Guide for efficient reading of a scientific article - Erika Sierra-Ruelas; Barbara Vizmanos Lamotte (Revista Información Científica)
Reading scientific articles is a fundamental skill for students, teachers and professionals in science. Sometimes the task of reading and understanding these texts can be overwhelming due to the amount of technical information and specialized language. However, with the right approach and consistent practice, it is possible to develop a deeper understanding and effective reading of these articles.